Differences in skeletal muscle loss caused by cytotoxic chemotherapy and molecular targeted therapy in patients with advanced non‐small cell lung cancer. Issue 1 (25th October 2017) - Kakinuma, Kazutaka; Tsuruoka, Hazime; Morikawa, Kei; Furuya, Naoki; Inoue, Takeo; Miyazawa, Teruomi; Mineshita, Masamichi
Abstract : Background: Recent studies have revealed a reduction in the skeletal muscle area in patients with advanced non‐small cell lung cancer (NSCLC) after chemotherapy. EGFR and ALK tyrosine kinase inhibitor (TKI)‐based therapies are less cytotoxic than chemotherapy, but differences in skeletal muscle mass between patients receiving EGFR and ALK TKI therapies and patients receiving cytotoxic chemotherapy have not yet been reported. Methods: Data of pathologically proven NSCLC patients were reviewed, and chest computed tomography and/or positron emission tomography‐computed tomography images obtained from January 2012 to December 2014 were selected. Patients were divided into two groups: cytotoxic chemotherapy (CG) and molecular targeted (MG). Muscle mass was measured with a single cross‐sectional area of the muscle at the third lumber vertebra (L3MA). To estimate skeletal muscle changes during chemotherapy, we defined the following L3 skeletal muscle index (L3SMI) ratio: post L3SMI/pre L3SMI. Differences in the SMI ratio between the groups were evaluated using the Wilcoxon signed‐rank test. Results: Sixty‐five patients were included in this study: 44 patients received cytotoxic chemotherapy and 21 received molecular targeted therapy (EGFR and ALK TKI). The loss of L3MA in the CG was higher than in the MG ( P = 0.03). In the CG, the L3SMI ratio defined to evaluate skeletal muscle mass changes was significantly lower than in the MG ( P = 0.0188). Conclusion: Our results suggest that skeletal muscle loss during first‐line therapy was significantly different between patients receiving cytotoxic chemotherapy and those receiving TKIs. Specifically, skeletal muscle loss was lower in patients receiving TKIs than in patients receiving cytotoxic chemotherapy.